FORMATION, DEVELOPMENT AND CRISIS OF THE KUSHAN KINGDOM - Sobirov Jamshidbek (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
this article briefly touches on the events from the founding of the ancient Kushan Kingdom to its development and until the crisis.